Yam Bean Seed Extract: An Alternative to Chemical Insecticide in Managing Cereal Aphid in Barley - Gouri Shankar Giri; Ashish Narayan; R.S. Singh; P. P. Singh; Neeraj Kumar; R. Prasad (JOURNAL OF ROOT CROPS, 2022)
Barley is an important cereal grown in Northern India, particularly during the rabi season. Nowadays, the aphid (Sitobium avenae) has emerged as a major key pest because of anthropogenic climate change and natural variability, which was considered as a minor pest during the past decade. An experiment was conducted at Research farm, Tirhut College of Agriculture,Dholi to evaluate the efficacy of tuber crop based bio-pesticide against aphid in barley. Bio-pesticides based on yam bean and cassava such as yam bean seed extract and powder, cassava leaf extract, and tuber rind extract along with chemical insecticide (dimethoate) were evaluated. Among them, two sprays of yam bean seed extract @ 5% at an interval of 15 days was found to be the most effective in managing the aphid population, which was at par with that of chemical insecticide dimethoate @ 0.05% and found to be safe for natural enemies particularly ladybird beetle and spider which are considered as a major predator of aphid in this ecosystems.